On Perspectiving in Cognitive Grammar and Communicative Dynamism - Sunarto, Emanuel (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2012)
The article is concerned with the concept of âperspectiveâ in Cognitive Grammar and Communicative Dynamism. To the former, âperspectiveâ is understood in the realm of cognitive concepts such as space, motion, locationality, directionality, importance, and focus ascribable to a particular sentence segment. To the latter, âperspectivingâ is a matter of valuating, viz. assigning informational value to a sentence segment as a part of a distributional field of communicative dynamism. The two streams of thought evidently hold different constructs per-taining to the term âperspectiveâ: conceptual-categorial on the one hand, and functional-informational on the other. However, the two seem to agree when âperspectivingâ is concerned with the notion of importance and focus or rhematization.Â DOI: https://doi.org/10.24071/llt.2012.150106